2006
DOI: 10.1021/bi0518500
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Skeletal Muscle S1-Myosin ATPase by Peroxynitrite

Abstract: Exposure of myosin subfragment 1 (S1) to 3-morpholinosydnonimine (SIN-1) produced a time-dependent inhibition of the F-actin-stimulated S1 Mg 2+ -ATPase activity, reaching 50% inhibition with 46.7 ( 8.3 µM SIN-1 for 8.7 µM S1, that is, at a SIN-1/S1 molar ratio of approximately 5.5. The inhibition was due to the peroxynitrite produced by SIN-1 decomposition because (1) decomposed SIN-1 was found to have no effect on S1 ATPase activity, (2) addition of SIN-1 in the presence of superoxide dismutase and catalase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 70 publications
2
46
2
Order By: Relevance
“…These results pointed out that F-actin is between 10-and 20-fold more sensitive to peroxynitrite than other proteins of relevance to muscle bioenergetics reported so far, like creatine kinase [27], myosin [24], and sarcoplasmic reticulum Ca 2+ -ATPase [21], and point out that actin filaments can be seen as a primary target in the impairment of muscle contraction by oxidative insults promoting a rise of peroxynitrite. …”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…These results pointed out that F-actin is between 10-and 20-fold more sensitive to peroxynitrite than other proteins of relevance to muscle bioenergetics reported so far, like creatine kinase [27], myosin [24], and sarcoplasmic reticulum Ca 2+ -ATPase [21], and point out that actin filaments can be seen as a primary target in the impairment of muscle contraction by oxidative insults promoting a rise of peroxynitrite. …”
Section: Resultsmentioning
confidence: 69%
“…1C), and (iii) hydrogen peroxide produced during SIN-1 decomposition in the buffer used in these experiments was lower than 0.5 lM and catalase did not prevent against the depolymerization of F-actin by exposure to SIN-1 (results not shown). From the kinetics of peroxynitrite production during SIN-1 decomposition under these experimental conditions [15,24] it follows that: (1) exposure of F-actin to peroxynitrite fluxes as low as 50-100 nM during 1-2 h produced nearly 50% F-actin depolymerization, and (2) the IC 50 for F-actin depolymerization takes place at a molar ratio of peroxynitrite/actin monomer close to 2.…”
Section: Resultsmentioning
confidence: 94%
“…Both are located in a critical ␣-helix in myosin (34) where covalent modifications of either cysteine typically lead to complete inhibition of myosin (24,35). Tiago et al (39) reported that myosin may be inactivated by ONOO Ϫ through oxidative modification of one of the reactive cysteines, perhaps to sulfenic acid (1), leading to partial unfolding of the protein. Consistent with this, our data show a decrease in reactive cysteines in myosin heavy chain purified from remote-zone samples.…”
Section: Discussionmentioning
confidence: 99%
“…Free radicalinduced oxidative modifications of proteins can alter their functional or structural properties (Bolli and Marbán 1999;Kloner and Jennings 2001a, b;Tiago et al 2006;Solaro 2007;Murphy et al 2008;Hertelendi et al 2008;Ding et al 2011;Gao et al 2012;Alegre-Cebollada et al 2014). These modifications modulate muscle force production and regulate passive stiffness in vitro (Bolli and Marbán 1999;Kloner and Jennings 2001a, b;Tiago et al 2006;Solaro 2007;Murphy et al 2008;Hertelendi et al 2008;Ding et al 2011;Gao et al 2012;Alegre-Cebollada et al 2014). Protein oxidation generally occurs at the reactive thio-moieties of cysteine residues (or to a lesser extent methionine), which can be modified through either reversible or irreversible oxidative states (Fig.…”
Section: •-mentioning
confidence: 99%
“…The myosin ATPase activity is the driving enzyme of the cross-cycle and was shown to be modified upon S-glutathionylation at different MHC sites (Passarelli et al 2008). Indeed, oxidation of two cysteines near the catalytic centre of the subfragment 1 (S1)-domain in MHC (Cys 697 and Cys 707 ) results in a strong inhibition of S1-ATPase activity and reduces maximal force (Tiago et al 2006). Elevated levels of glucose adducts (glycosylation) have been found on the MHC in post-mortem hearts of diabetic patients, and carbonylation of MHC as a result of reactive carbonyl species (RCS) has been consistently found in rat hearts during diabetes (Shao et al 2010).…”
Section: Impact Of Oxidative Stress On Cardiomyocyte Stiffness Sarcommentioning
confidence: 99%